اليقظة الإستراتيجية ضرورة حتمية للاستمرار في البيئة المعاصر - مريم بلحاج مريم بلحاج (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(–scale-factor)*120.86px); top: calc(var(–scale-factor)*481.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923758);" role="presentation">his study exam<span dir="ltr" style="left: calc(var(–scale-factor)*187.82px); top: calc(var(–scale-factor)*481.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914578);" role="presentation">ines what <span dir="ltr" style="left: calc(var(–scale-factor)*229.37px); top: calc(var(–scale-factor)*481.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939405);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*239.09px); top: calc(var(–scale-factor)*481.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927941);" role="presentation">the concept of the business intelligence with major differences <span dir="ltr" style="left: calc(var(–scale-factor)*62.28px); top: calc(var(–scale-factor)*498.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935528);" role="presentation">between researchers and organizations, where this concept reflects a management philosophy without a <span dir="ltr" style="left: calc(var(–scale-factor)*62.28px); top: calc(var(–scale-factor)*515.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944509);" role="presentation">specific model in the current fluctuations and highly and rapidly changing wor<span dir="ltr" style="left: calc(var(–scale-factor)*382.87px); top: calc(var(–scale-factor)*515.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931191);" role="presentation">ld. So, technical dimension <span dir="ltr" style="left: calc(var(–scale-factor)*62.28px); top: calc(var(–scale-factor)*533.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963529);" role="presentation">which represents information technology, is a double-<span dir="ltr" style="left: calc(var(–scale-factor)*288.65px); top: calc(var(–scale-factor)*533.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945829);" role="presentation">edged sword negative and positive, needs to use <span dir="ltr" style="left: calc(var(–scale-factor)*62.28px); top: calc(var(–scale-factor)*550.54px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929775);" role="presentation">quality to achieve high results, which reflected the administrative dimension of the concept. On this basis, <span dir="ltr" style="left: calc(var(–scale-factor)*62.28px); top: calc(var(–scale-factor)*567.82px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907563);" role="presentation">instead of conside<span dir="ltr" style="left: calc(var(–scale-factor)*135.26px); top: calc(var(–scale-factor)*567.82px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919467);" role="presentation">ring the concept of the business intelligence science or programming, it is considered an <span dir="ltr" style="left: calc(var(–scale-factor)*62.28px); top: calc(var(–scale-factor)*584.98px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89691);" role="presentation">art or a strategy based on the human element, which is the basis of excellence among organizations.